PENGEMBANGAN KREATIVITAS PENDIDIKAN ISLAM DI INDONESIA (TELAAH URGENSI PROSES) - Mahmudah Mahmudah (Institut Agama Islam Negeri Purwokerto, 2014)
Nowadays, the change and the development of society run faster and more dispersely than before. In this era of globalization, Islamic education, as a means to bring out a competent human capital that can compete in the era of 21st century, needs to pay closer attention to the